SUMO - nonclassical ubiquitin - Melchior, Frauke (Annual review of cell and developmental biology, 2000)
SUMO (small ubiquitin-related modifier) is the best-characterized member of a growing family of ubiquitin-related proteins. It resembles ubiquitin in its structure, its ability to be ligated to other proteins, as well as in the mechanism of ligation. However, in contrast to ubiquitination-often the first step on a one-way road to protein degradation-SUMOlation does not seem to mark proteins for degradation. In fact, SUMO may even function as an antagonist of ubiquitin in the degradation of selected proteins. While most SUMO targets are still at large, available data provide compelling evidence for a role of SUMO in the regulation of protein-protein interactions and/or subcellular localization.
Gesehen am 13.03.2023